Cover Image, Volume 30, Issue 8. (August 2017) - Wiggermann, Vanessa; Hametner, Simon; Hernández‐Torres, Enedino; Kames, Christian; Endmayr, Verena; Kasprian, Gregor; Höftberger, Romana; Li, David K.B.; Traboulsee, Anthony; Rauscher, Alexander
Abstract : The cover image, by Vanessa Wiggermann et al., is based on the Research Article Susceptibility-sensitive MRI of multiple sclerosis lesions and the impact of normal‐appearing white matter changes, DOI:10.1002/nbm.3727 .